Pseudocyesis as a healing mechanism for psychological trauma - Georgia Nektaria Porfyri; Anastasia Konsta; Anthoula Tsolaki; Ioannis Diakogiannis; Ioanna Ierodiakonou-Benou (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
Pseudocyesis, a rare condition characterized by clinical signs and symptoms of pregnancy except for the actual existence of a fetus, is a somatic symptom disorder associated with a variety of biological, psychological and social factors. The present report aims to present the case of a 45-year old patient with pseudocyesis from a psychodynamic perspective. According to a psychodynamic perspective and based on patient’s history, pseudocyesis functioned as a mental healing mechanismfor the trauma of long-standing infertility, the trauma of eight unsuccessful and painful in vitro fertilization attempts and above all, the trauma of finally giving birth to a non-healthy child.